2017
DOI: 10.1021/jacs.7b04930
|View full text |Cite
|
Sign up to set email alerts
|

Cation Dynamics in Mixed-Cation (MA)x(FA)1–xPbI3 Hybrid Perovskites from Solid-State NMR

Abstract: Mixed-cation organic lead halide perovskites attract unfaltering attention owing to their excellent photovoltaic properties. Currently, the best performing perovskite materials contain multiple cations and provide power conversion efficiencies up to around 22%. Here, we report the first quantitative, cation-specific data on cation reorientation dynamics in hybrid mixed-cation formamidinium (FA)/methylammonium (MA) lead halide perovskites. We use N,H, C, andH solid-state MAS NMR to elucidate cation reorientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
403
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 246 publications
(434 citation statements)
references
References 51 publications
28
403
3
Order By: Relevance
“…We have previously shown that solid-state NMR is well suited to probe the atomic-level microstructure of multicomponent lead halide perovskites, [26][27][28][29] yet this approach has not been systematically employed to analyze the structural features of layered 2D perovskites so far. We have previously shown that solid-state NMR is well suited to probe the atomic-level microstructure of multicomponent lead halide perovskites, [26][27][28][29] yet this approach has not been systematically employed to analyze the structural features of layered 2D perovskites so far.…”
Section: Structural Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that solid-state NMR is well suited to probe the atomic-level microstructure of multicomponent lead halide perovskites, [26][27][28][29] yet this approach has not been systematically employed to analyze the structural features of layered 2D perovskites so far. We have previously shown that solid-state NMR is well suited to probe the atomic-level microstructure of multicomponent lead halide perovskites, [26][27][28][29] yet this approach has not been systematically employed to analyze the structural features of layered 2D perovskites so far.…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…[16,26,27] Since the A/FA and A′/FA phases contain a 3D perovskite phase, 14 N MAS NMR can yield information on whether or not this phase is microscopically modified by the presence of the spacer. In the case of 3D perovskites, 14 N MAS NMR spectra feature a spinning sideband (SSB) pattern that corresponds to the central cation reorienting on the picosecond timescale within the cubooctahedral cavity.…”
Section: Structural Characteristicsmentioning
confidence: 99%
“…For each rotation mode about the principal axes of the molecule, the other two rotation angles are fixed (for φ 1 rotations, φ 2 = φ 3 = 0; for φ 2 rotations, φ 1 = (0, 90 29 Reported reorientation times from GHz spectroscopy, quasi-elastic neutron scattering (QENS), ab initio molecular dynamics (MD), and 14 N NMR are presented for comparison. 15,16,23,24,36,42,73 14 reorientation. In particular, it is intriguing to consider if the differing barriers to molecular dipole rotation and differing dipole moments lead to important differences between FAPbI 3 and MAPbI 3 on timescales relevant to exciton dissociation, interaction of charge carriers with polar optical phonons or polarons, or momentum separation of excited electrons and holes due to possible dynamic Rashba-Dresselhaus effects.…”
Section: 41mentioning
confidence: 99%
“…Our group has very recently used solid-state NMR to elucidate microscopic phase composition and segregation in MA/FA HOPs. 26 …”
Section: Introductionmentioning
confidence: 99%